AN ACCOUNT OF GOVERNOR ANIES BASWEDAN’S PERFORMANCE ON INCLUSIVE ECONOMIC GROWTH IN DKI JAKARTA (2017-2021) - Sahruddin Lubis; Hari Zamharir (Journal of Social Political Sciences, 2022)
Adopting the principles of good corporate governance by state governments in times of influence of corporations is crucial given the mandate of the Constitution that government agencies must adhere to. Beginning with “abnormal” politics of the elected governor in 2017, Anies encounters challenges both politically and the choice of the road to inclusive economic development. This paper makes an account of Anies’s performance in executing the tasks. The method of the study employs qualitative research method, with secondary data to be analyzed through meta-analysis. The concepts of good corporate governance and inclusive economic growth are the two concepts to look into the performance. It is our finding that amidst controversies in the early days in office when sociological legitimacy was questioned, Anies eventually gains performance legitimacy as has been reflected by several awards by authorities in their respective government and international agencies.